PNEUMONIA AND CARDITIS IN CHILDREN: COMPLEX IMPACT ON PROGNOSIS - Mukhammadiev Ismail Sulaimanovich,; Shavazi Ramiz Nuralievich, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Background. Severe and protracted pneumonia is often associated with comorbidities. These conditions significantly alter the disease's manifestations, reduce the effectiveness of standard treatments, and worsen the prognosis. In this context, inflammatory cardiovascular diseases, particularly carditis, are among the most unfavorable factors contributing to the development of exacerbation syndrome.Study Objective: To investigate the impact of concomitant carditis on the clinical presentation, complication rate, and outcomes of pneumonia in children.Materials and Methods: The study included 40 children with community-acquired pneumonia, who were divided into two comparison groups. The study group included 20 children with pneumonia associated with carditis, while the comparison group included 20 children with pneumonia without concomitant cardiac disease.